Financial Toxicity and Kidney Disease in Children and Adults: A Scoping Review - Siligato R; Gembillo G; De Giorgi A; Di Maria A; Scichilone LM; Capone M; Vinci FM; Nicoletti S; Bondanelli M; Malaventura C; Storari A; Santoro D; et al. (International Journal of Nephrology and Renovascular Disease)
Rossella Siligato,1,2 Guido Gembillo,2,3 Alfredo De Giorgi,4 Alessio Di Maria,1 Laura Maria Scichilone,1 Matteo Capone,1,5 Francesca Maria Vinci,1,5 Simone Nicoletti,1 Marta Bondanelli,5 Cristina Malaventura,5 Alda Storari,1,5 Domenico Santoro,3 Sara Dionisi,6 Fabio Fabbian1,5 1Nephrology Unit, University Hospital of Ferrara, Ferrara, Italy; 2Department of Biomedical, Dental, Morphological and Functional Imaging Sciences, University of Messina, Messina, Italy; 3Unit of Nephrology and Dialysis, Department of Clinical and Experimental Medicine, University of Messina, Messina, Italy; 4Internal Medicine, University Hospital of Ferrara, Ferrara, Italy; 5Department of Medical Sciences, University of Ferrara, Ferrara, Italy; 6Nursing, Technical and Rehabilitation, Department DATeR Azienda Unità Sanitaria Locale Di Bologna, Bologna, ItalyCorrespondence: Fabio Fabbian, Department of Medical Sciences, via Luigi Borsari, 46, Ferrara, Italy, I-44124, Tel +39 0532 239385, Email f.fabbian@ospfe.itPurpose: Social determinants of health have been related with kidney diseases and their outcomes. Financial toxicity (FT) refers to the negative impact of health care costs on clinical conditions. This scoping review aimed to evaluate the literature linking FT with renal diseases.Patients and Methods: We Included all studies analyzing FT and renal disease recorded in PubMed, Embase and Google Scholar between 2013 and 2023. The research question was formulated with reference to the acronym PCC (Problem, Concept and Contest). For each included study, we considered the study design, the population and main results from different populations with distinct renal conditions and the results were summarized in four tables.Results: Socioeconomic deprivation was the main cause of FT, and the majority of studies on the relationship between FT and chronic kidney disease (CKD) were conducted in the USA (4 studies evaluated the pediatric population and 6 studies included adults). Three studies reported the impact of FT on nephrolithiasis, and 3 studies analyzed the link between FT and renal tumors. The methods used for detecting FT differed and were based on consultations, questionnaires, expenditures and database records analysis. The COmprehensive Score for financial Toxicity (COST) questionnaire was used in 7 studies (43%), and the prevalence of FT was reported to be high in children and adults.Conclusion: Although the quality of the selected study is limited, due to different populations investigated and heterogeneity in detecting FT, the latter seems to be a frequent finding in people with renal disease. Health care professionals should recognize socioeconomic deprivation as the major cause of FT. Detecting FT could help in prioritizing patient-centered care in populations with renal diseases through the development of strategies aimed at improving care for people with kidney diseases.Plain Language Summary: Social determinants of health, especially poverty, social environmental stressors and psychological factors, are increasingly recognized as significant determinants of kidney diseases and their outcomes. Financial toxicity (FT) refers to the negative impact of health care costs on clinical conditions. The relationship between FT and renal disease is not completely understood. With this scoping review, we evaluated all published papers between 2013 and 2023 on this item. We analyzed 16 studies and found that FT is common in pediatric and adult CKD patients and in patients with nephrolithiasis and renal tumors. For patients with kidney disease, FT represents a significant burden, both through the direct costs of disease management and treatment and through indirect costs such as the loss of income due to missed work and expenses for transportation and accommodations near outpatient clinics. Finally, it should be noted that in different countries, it is difficult for people with kidney disease to obtain health insurance coverage. Health care professionals need to improve their knowledge about the relationship between FT and renal disease; there is a paucity of data regarding the effects of FT on different outcomes, although this nonmedical risk factor can negatively influence kidney health and quality of life. Further studies involving different professionals able to consider environmental, physical and emotional risk factors are needed. Keywords: financial toxicity, financial burden, financial hardship, renal disease, chronic kidney disease